Efek Extracorporeal Membrane Oxygenation Terhadap Hemodinamik Pasien Kritis Dengan Acute Respiratory Distress Syndrome di Intensive Care Unit : Literature Review: Efek Extracorporeal Membrane Oxygenation Terhadap Hemodinamik Pasien Kritis Dengan Acute Respiratory Distress Syndrome di Intensive Care Unit : Literature Review - Nasrun Pakaya; Iin Pratiwi Adjami; Susanty Monoarfa (Yayasan Ahmad Mansyur Nasirah, 2022)
Introduction: Acute Respiratory Distress Syndrome (ARDS) is a lung disease characterized by the occurrence of hypoxia and stiff lungs and increased vascular permeability. One of the collaborative measures that can be used is Extracorporeal Membrane Oxygenation (ECMO). The purpose of this literature study is to synthesize evidence or literature on the effects of extracorporeal membrane oxygenation (ECMO) on hemodynamics in critically ill patients with acute respiratory distress syndrome (ARDS). This literature review research method uses the PUBMED database of 8 journal articles, Science direct 3 journal articles, and research gate 3 journal articles. The results showed that there was a relationship between Extracorporeal Membrane Oxygenation (ECMO) and the patient's respiratory and hemodynamic status. The use of Extracorporeal Membrane Oxygenation (ECMO) can largely improve the respiratory status and hemodynamic status of critically ill patients with Acute Respiratory Distress Syndrome (ARDS). Most of the journal articles analyzed show that ECMO can improve respiratory status compared to the hemodynamic status of critically ill patients with Acute Respiratory Distress Syndrome (ARDS). Pendahuluan: Acute Respiratory Distress Syndrome (ARDS) termasuk penyakit paru ditandai dengan terjadinya hipoksia serta paru-paru yang kaku dan peningkatan permeabilitas pembuluh darah . Salah satu tindakan kolaboratif yang dapat digunakan yaitu Extracorporeal Membrane Oxygenation (ECMO). Tujuan studi literature ini adalah Untuk mensintesis bukti-bukti atau literatur tentang Efek Extracorporeal Membrane Oxygenation (ECMO) Terhadap Hemodinamik Pasien Kritis Dengan Acute Respiratory Distress Syndrome (ARDS). Metode penelitian literature riview ini menggunakan data base PUBMED 8 artikel jurnal, Science direct 3 artikel jurnal, dan research gate 3 artikel jurnal. Hasil penelitian menunjukan ada hubungan Extracorporeal Membrane Oxygenation (ECMO) dengan status pernapasan dan hemodinamik pasien. Penggunaan Extracorporeal Membrane Oxygenation (ECMO) sebagian besar dapat meningkatkan status pernapasan serta status hemodinamik pasien kritis dengan Acute Respiratory Distress Syndrome (ARDS). Sebagian besar artikel jurnal yang dianalisis menunjukkan ECMO dapat meningkatkan status pernapasan dibandingkan dengan status hemodinamik pasien kritis dengan Acute Respiratory Distress Syndrome (ARDS).